Studi Model Distribusi Pencemaran di Pantai Utara Jawa Tengah Menggunakan Model MIKE 21 ECOLab - Adam Rus Nugroho; Rudhy Akhwady; Dimas Metakaryanto; Fahrul Yahya (Teknik Lingkungan Universitas Islam Indonesia, 2016)
Central Java has several estuaries which highly populated in their area, generating high load of waste water discharge. Research conducted on two of the estuaries, Comal estuary in Pemalang and Garang estuary in Semarang. Waste water discharge from population around upstream river of Comal and Garang pollute both estuaries, which are in north coast of Central Java. The aim of this research is to determine the amount of pollutants which enter the estuary and become sediment in Comal and Garang river estuary. The amount of pollution has been analyzed by QUAL2Kw program which then the result would be input data for sediment analysis using MIKE 21 ECOLab program. The result of research state that Comal estuary has BOD concentration of 4.26 mg/L on west season and 4.21 mg/L on east season. While Garang estuary has BOD concentration of 18.21 mg/L on west season and 4.73 mg/L on east season.